The debt tax shield, economic growth and inequality - Marcel Fischer; Bjarne Astrup Jensen (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
We study the implications of the corporate debt tax shield in a growth economy that taxes household income and firm profits and redistributes tax revenues in an attempt to harmonize the lifetime consumption opportunities of households that differ in their endowments. Our model predicts that the debt tax shield (1) increases the risk-free rate, (2) leads to a higher growth rate of the economy, and (3) increases the degree of disparity in households' lifetime consumption opportunities. We further show that the debt tax shield affects the tradeoff between the goals of achieving a high growth rate of the economy and a low degree of inequality and quantify this tradeoff.
Keywords: E21; E23; G11; H23; H31; H32; 330; debt tax shield; macroeconomic growth; redistributive tax system